Phenology and yield of cape gooseberry cultivated in open field in subtropical environment - Weber, Anderson; Soldateli, Francis Júnior; Barcelar, Mateus Gusmão; Moura, Andrei Soares; Bitencourt, Alex Oliveira (Comunicata Scientiae, 2021)
Cape gooseberry (Physalis peruviana L.) is a plant that presents fruit with high aggregate value and expressive levels of beneficial components to the human health. However, the lack of knowledge of the phenological phases limits the expansion of the crop under subtropical conditions, especially in open field production, despite it is a typical tropical plant. This research aimed to evaluate the phenological stages related the growth and the production of cape gooseberry cultivated under subtropical environment in an open field production system. The phenological stages were determined by the evaluations from the plant’s emerging date until it is senescence. The cape gooseberry cycle comprised 254 days with a total of 3,843.6 °C day. Cape gooseberry reached a maximum of 173 leaves, 193 cm height, and 1.16 cm stem diameter. The plastochron at the vegetative phase was 15.7 °C day node-1 and at the reproductive phase 20.6 °C day node-1. The fruit reached the harvest point with 3,045.3 °C day, corresponding to 179 days from the sowing or 100 days after transplantation, and the production period was extended for 60 days. Under the edaphoclimatic conditions (subtropical region), the production was 151.2 g per plant with estimated yield of 1,007.8 kg ha-1.